Poor availability of essential medicines for women and children threatens progress towards Sustainable Development Goal 3 in Africa. (5th October 2019) - Droti, Benson; O'Neill, Kathryn Patricia; Mathai, Matthews; Yao Tsidi Dovlo, Delanyo; Robertson, Jane
Abstract : Background: Most maternal and child deaths are preventable or treatable with proven, cost-effective interventions for infectious diseases and maternal and neonatal complications. In 2015 sub-Saharan Africa accounted for up to 66% of global maternal deaths and half of the under-five deaths. Access to essential medicines and commodities and trained healthcare workers to provide life-saving maternal, newborn and post-natal care are central to further reductions in maternal and child mortality. Methods: Available data for 24 priority medicines for women and children were extracted from WHO service availability and readiness assessments conducted between 2012 and 2015 for eight countries in sub-Saharan Africa. The mean availability of medicines in facilities stating they provide services for women or children and differences by facility type, ownership and location are reported. Results: The mean availability of 12 priority essential medicines for women ranged from 22% to 40% (median 33%; IQR 12%) and 12 priority medicines for children ranged from 28% to 57% (median 50%; IQR 14%). Few facilities (<1%) had all nominated medicines available. There was higher availability of priority medicines for women in hospitals than in primary care facilities: range 32%–80% (median 61%) versus 20%–39% (median 23%) and for children's medicines 31%–71% (median 58%) versus 27%–57% (median 48%). Availability was higher in public than private facilities: for women's medicines, range 21%–41% (median 34%) versus 4%–36% (median 27%) and for children's medicines 28%–58% (median 51%) versus 5%–58% (median 46%). Patterns were mixed for rural and urban location for the priority medicines for women, but similar for children's medicines. Conclusions: The survey results show unacceptably low availability of priority medicines for women and children in the eight countries. Governments should ensure the availability of medicines for mothers and children if they are to achieve the health sustainable development goals.